Associação entre o Índice Inflamatório da Dieta, parâmetros crononutricionais e fatores de risco cardiovascular em mulheres sobreviventes ao câncer de mama em terapia endócrina - Nunes, Fernanda Silva Mazzutti (2024)
Introduction: Breast cancer (BC) survivors have a higher risk of developing and dying from cardiovascular diseases (CVDs) than the general population. The Dietary Inflammatory Index (DII) and chrononutritional aspects, such as energy and macronutrient distribution throughout the day, impact metabolic health and the development of CVDs, but the association of these variables with cardiovascular risk factors in BC survivors has not yet been studied. Objective: This thesis had three main objectives: 1) Evaluate the association of DII with cardiovascular risk factors; 2) Evaluate the association of energy and macronutrient distribution throughout the day with cardiovascular risk factors; 3) Evaluate the association between cardiovascular risk parameters. Material and Methods: A cross-sectional study was carried out with 84 female BC survivors undergoing endocrine therapy with Tamoxifen. The DII was calculated from three 24-hour dietary recalls (24HR). Furthermore, the distribution of energy and macronutrients throughout the day was calculated as a percentage according to three eating windows - morning (05:00h-10:59h), afternoon (11:00h) 00h-17:59h), and evening (18:00h-00:30h). Caloric midpoint time, highest caloric meal time and first and last meal time were also evaluated. The cardiovascular risk factors assessed were body mass index (BMI), measures of abdominal adiposity - waist circumference (WC), waist-to-height ratio (WHtR) and conicity index (CI), body composition through electrical bioimpedance examination, biochemical tests, obtaining serum levels of fasting blood glucose, lipid profile, C-reactive protein and complete blood count. In addition, lipid accumulation product (LAP), visceral adiposity index, monocyte-lymphocyte ratio, neutrophil-lymphocyte ratio and platelet-lymphocyte ratio were calculated. The presence of metabolic comorbidities was assessed using a semi-structured questionnaire. Generalized linear models were used to verify the association between the variables. Results: The DII was positively associated with triglycerides (TG) (p = 0.045) and neutrophil-lymphocyte ratio (p = 0.042). Greater consumption of energy and macronutrients in the morning was associated with lower BMI (p = 0.011), WC (p = 0.004) and LAP (p = 0.025), contributing to lower cardiovascular risk, unlike their more concentrated consumption in the evening, which was associated with a higher body fat percentage (p = 0.001). Women with higher BMI, abdominal adiposity and worse body composition had a worse lipid profile (p < 0.005). Furthermore, the presence of comorbidities was associated with higher BMI (p = 0.002), WC (p < 0.001), VLDL-C (p < 0.001) and TG (p = 0.001). Conclusion: Women with a more pro-inflammatory diet and greater energy consumption in the evening have a worse metabolic profile. Furthermore, worse body composition and the presence of comorbidities were associated with a worse lipid profile.